Reframing philosophical views on freedom, choice, perfectibility and self-realisation in selected contemporary post-apocalyptic fictions - Zahra, Rezaei (2021)
From 18th century onwards, due to the advancement of social consciousness and individual choice, the issues of freedom, choice and self-realisation have become the main topic for a great number of novelist and philosophers who attempt to criticise totalitarian system of society and depict the real situation of their time. Through fiction, the novelists challenge readers to think differently about their social and political circumstances, and to react to the changes that have happened around the world. These issues have been the focus of scholarships on contemporary fictions set in a dystopian world (Bollinger 2007, Humann 2010). More importantly, the selected contemporary fictions, namely Parable of the Talents (1998) by Octavia E. Butler, Mara and Dann: An Adventure (1999) by Doris Lessing, The Road (2006) by Cormac McCarthy and The Pesthouse (2007) by Jim Crace, have been classified within post-apocalyptic fiction genre where the authors depict social and environmental disintegration in the far distant future. The selected novels revolve around the lives of the protagonists who face not only environmental changes but also gender and race discriminations, destructions of communities and government corruptions. In the works of literature, considerable scholarship on the notions of dystopia/ utopia as well as the degradation of human identity and subjectivity, have been conducted on post-apocalyptic fiction (Bollinger, 2007; Edwards, 2009; De Bruyn, 2010; Søfting, 2013). Yet, more research needs to be conducted on post-apocalyptic texts using the social contract approach through the concepts of self-realisation, freedom and choice because there is a lack of scholarship on how authors portray characters who wish for a just society in order to act freely and make choices for perfectibility which is achievable through social agreement. Accordingly, I have decided to explore these concepts in the selected science fictions. I will use the conceptual frameworks of freedom, choice and perfectibility by John Rawls and Jean- Jacques Rousseau, and self-realisation by Karl Marx. The objectives of the study are to discover how the protagonists of the texts interact with society and externalise their personal potential for perfectibility, to examine the authors’ depictions of moral freedom, choice and self–realisation through the protagonists of the selected texts and, lastly, to explore how the model of perfect society by Rousseau and Rawls are reflected through the protagonists. Through the frameworks, the analyses examine how the characters can change and develop psychologically and physically, or whether they can attain perfectibility if they have freedom and independency. As such, this study investigates the selected characters’ potentials and abilities for making choices and changing their world after freedom and realisation of the selves. More specifically, Lauran Oya Olamina in Parable of the Talents becomes a leader who spreads her new religion, Earthseed, in the world and sends people to the stars; Mara and Dann in Mara and Dann: An Adventure can change their destinies and create a small self-sufficient community; the father in The Road fails to reach his ideal society but his son can change his own destiny and find good people; and Margaret and Franklin in The Pesthouse cannot change their society, but they find their home, America, a good place for starting a new life. Therefore, this study has found how the various understanding of the concepts of freedom, choice and self-realisation are used to highlight the selected characters’ development and perfectibility in the selected post-apocalyptic fictions, and also to demonstrate the adoption of conceptual frameworks for analysing human connection with others and the environment (nature) in the selected post-apocalyptic novels. Findings of this study suggest that freedom, choice and self-realisation can further be examined based on views by other philosophers, such as David Gauthier, and many other science fictions written to this day. Furthermore, the selected authors chosen for this study have published a number of science fictions that may open up opportunities for future researchers to examine them from the aspects of dystopia and utopia